Anatomical and functional correlates of persistent pain in Parkinson's disease. Issue 12 (5th October 2016) - Polli, Andrea; Weis, Luca; Biundo, Roberta; Thacker, Michael; Turolla, Andrea; Koutsikos, Kostantinos; Chaudhuri, K. Ray; Antonini, Angelo
ABSTRACT: Background: The pathophysiology of pain in Parkinson's disease (PD) is still poorly understood, although it is conceivable that supraspinal mechanisms may be responsible for pain generation and maintenance. Methods: We examined brain functional and anatomical changes associated with persistent pain in 40 PD patients, 20 with persistent pain and 20 without pain. We also examined 15 pain‐free healthy participants of similar age, gender, and cognitive state as a control group. We assessed pain by the King's Parkinson's Pain Scale, the Visual Analogue Scale for pain, and the Leeds Assessment for Neuropathic Symptoms and Sign. All patients underwent structural, diffusion tensor imaging, and resting‐state functional MRI. We compared clinical characteristics, whole‐brain cortical thickness, subcortical volumes, diffusion tensor imaging scalar measures, and functional connectivity by network based statistics. Results: The group with PD and persistent pain showed significant thinning in the bilateral temporal pole, left‐medial orbitofrontal cortex, bilateral superior and left‐inferior parietal areas, pars orbicularis, and right superior frontal, posterior cingulated, and precentral cortex. There were no significant subcortical volume and white matter differences between PD subgroups. Functional MRI showed a decrease of brain activity in the left frontal inferior orbital in PD patients with persistent pain, with greater activity bilaterally in the cerebellum and in the right inferior temporal areas. Only PD patients with persistent pain showed an accumbens–hippocampus disconnection without white matter and subcortical alterations. Conclusions: We showed that persistent pain in PD is associated with supraspinal structural and functional changes. We also highlighted the contribution of frontal, prefrontal, and insular areas in nociceptive modulation and accumbens–hippocampus disconnection. © 2016 International Parkinson and Movement Disorder Society.